2015
DOI: 10.3233/ch-131761
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic deformability of erythrocytes at various shear stresses

Abstract: Red blood cell (RBC) deformability is greatly affected by the osmolality, and maximum deformability, which is determined as maximal elongation index (EI max ), is usually observed in isotonic conditions at high shear stresses (>20 Pa). Therefore, we examined osmotic RBC deformability over a range of shear stresses (0.5-20 Pa). We found that the RBC deformability at low shear stresses (1-3 Pa) was maximum in hypotonic conditions (225-250 mOsm/kg H 2 O), which is slightly lower than the normal range of osmolalit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…EI max is usually observed at isotonic conditions during high shear stress (>20 Pa). However, a recent study [15] reported that RBC deformability at low shear stress (1-3 Pa) was maximal in hypotonic conditions (225-250 mOsm/kg H 2 O), which is slightly lower than the normal range of osmolality in plasma (290-310 mOsm/kg H 2 O). The osmolality at EI max (O max ) was found to be dependent on applied shear stress, which could play an important role in microcirculation processes such as the Fåhraeus-Lindqvist effect [16].…”
Section: Osmotic Concentrationsmentioning
confidence: 89%
“…EI max is usually observed at isotonic conditions during high shear stress (>20 Pa). However, a recent study [15] reported that RBC deformability at low shear stress (1-3 Pa) was maximal in hypotonic conditions (225-250 mOsm/kg H 2 O), which is slightly lower than the normal range of osmolality in plasma (290-310 mOsm/kg H 2 O). The osmolality at EI max (O max ) was found to be dependent on applied shear stress, which could play an important role in microcirculation processes such as the Fåhraeus-Lindqvist effect [16].…”
Section: Osmotic Concentrationsmentioning
confidence: 89%
“…The least noisy readouts were obtained at 30 Pa. Choice of this supraphysiological shear stress levels for both machines had an impact of maximal deformability EImax, which was shown to increase with a growing shear stress, and on the ionic strength O_EI_max at which maximal deformability is reached (Heo et al, 2015;Nemeth et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The osmotic gradient ektacytometric measurements ( Heo et al, 2015 ; Nemeth et al, 2015 ; Huang et al, 2019 ) were obtained using the “osmoscan function” of the above optical rotational red cell analyzer device (LoRRca). The device generated a constant shear stress of 30 Pa while continuously aspirating the sample into the measurement site and while changing the osmolarity of the medium by using gradual mixtures of PVP solutions of 0 and 700 mOsmol/kg; therefore, the EI was continuously registered.…”
Section: Methodsmentioning
confidence: 99%
“…The device generated a constant shear stress of 30 Pa while continuously aspirating the sample into the measurement site and while changing the osmolarity of the medium by using gradual mixtures of PVP solutions of 0 and 700 mOsmol/kg; therefore, the EI was continuously registered. The parameters measured and calculated by the device (all at shear stress of 30 Pa) were as follows ( Heo et al, 2015 ; Nemeth et al, 2015 ; Huang et al, 2019 ):…”
Section: Methodsmentioning
confidence: 99%